The Idea of the Book in the Middle Ages Language Theory, Mythology, and Fiction - Gellrich, Jesse (Cornell University Press, 1987)
This book assess the relationship of literature to various other cultural forms in the Middle Ages. Jesse M. Gellrich uses the insights of such thinkers as Levi-Strauss, Foucault, Barthes, and Derrida to explore the continuity of medieval ideas about speaking, writing, and texts.